Investigation of the relationship between upper extremity musculoskeletal problems and occupational burnout in hairdressers - SARI, ZÜBEYİR (My University, 2022)
The aim of this study is to investigate which body parts are common musculoskeletal problems in hairdressers and to examine the relationship between upper extremity musculoskeletal problems and the level of occupational burnout. This cross-sectional study included 78 hairdressers with congenital or chronic musculoskeletal disease, no pregnancy, and no traumatic musculoskeletal problems in the last 6 months. After the demographic information of the participants was obtained, the Cornell Musculoskeletal Disorder Questionnaire (CMDQ) was used to determine the musculoskeletal system problems and the effects of these problems on work; Occupational burnout levels were evaluated with the Burnout Scale-Short Form (BS-SF). Of the participants, 26 (33.3%) were female hairdressers and 52 (66.7%) were male hairdressers. The body parts of the hairdressers with the highest musculoskeletal pain/suffering/discomfort were neck (n=46) and waist (n=45) regions. There was a moderate positive correlation between the musculoskeletal system problems and occupational burnout levels of the participants (r=0.387, p<0.01), and a high level positive correlation between upper extremity musculoskeletal problems and occupational burnout levels (r=0.584; p= 0.008) was recorded. Musculoskeletal disorders, especially upper extremity problems, were encountered in hairdressers. In addition, it is seen that musculoskeletal disorders and occupational burnout are closely related concepts. Implementing preventive rehabilitation programs for hairdressers and making ergonomic arrangements in the workplace may have positive effects on the musculoskeletal system and thus on professional satisfaction and pleasure.

Bu çalışmanın amacı, kuaförlerde kas-iskelet sistemi problemlerinin hangi vücut bölgelerinde sık görüldüğünü araştırmak ve üst ekstremite kas iskelet sistemi problemleri ile mesleki tükenmişlik düzeyi arasındaki ilişkiyi incelemektir. Kesitsel tipte tasarlanan bu çalışmaya konjenital kas iskelet sistemi hastalığı ve gebelik durumu olmayan, son 6 ay içinde travmatik kas iskelet sistemi problemi yaşamamış 78 kuaför dahil edildi. Katılımcıların demografik bilgileri alındıktan sonra, Cornell Kas İskelet Sistemi Rahatsızlığı Anketi (CKİSRA) ile kas-iskelet sistemi bu problemleri ve problemlerin işe etkisi; Tükenmişlik Ölçeği-Kısa Formu (TÖ-KF) ile mesleki tükenmişlik düzeyleri değerlendirildi. Katılımcıların 26’sı (%33,3) kadın, 52’si (%66,7) erkek kuaförüydü. Kuaförlerin kas iskelet sistemi ağrı/sızı/rahatsızlık hissinin en çok olduğu vücut bölgeleri boyun (n=46) ve bel (n=45) bölgeleriydi. Katılımcıların kas iskelet sistemi problemleri ile mesleki tükenmişlik düzeyleri arasında pozitif yönde orta düzey (r=0,387; p<0,01), üst ekstremite kas iskelet sistemi problemleri ile mesleki tükenmişlik düzeyleri arasında pozitif yönde yüksek düzey bir ilişki (r=0,584; p=0,008) kaydedilmiştir. Kuaförlerde başta üst ekstremite problemleri olmak üzere kas iskelet sistemi rahatsızlıklarına rastlandı. Ayrıca kas iskelet sistemi rahatsızlıkları ile mesleki tükenmişliğin birbiriyle yakından ilişkili kavramlar olduğu görülmektedir. Kuaförlere koruyucu rehabilitasyon programlarının uygulanmasının ve işyerlerinde ergonomik düzenlemeler yapılmasının kas iskelet sistemi ve dolayısıyla mesleki doyum ve tatmin üzerine pozitif etkileri olabilir.
Kuaförlerdeki üst ekstremite kas-iskelet sistemi problemleri ile mesleki tükenmişlik arasındaki ilişkinin incelenmesi
Keywords: Occupations; Musculoskeletal system; Burnout; Meslek; Kas iskelet sistemi; Tükenmişlik